2005
DOI: 10.1007/s11172-005-0360-y
|View full text |Cite
|
Sign up to set email alerts
|

Reversible luminescence thermochromism of dibenzoyl(methanato)boron difluoride

Abstract: Reversible luminescence thermochromism of dibenzoyl(methanato)boron difluoride was found. A substantial hypsochromic shift of the luminescence band maximum (60 nm) with a temperature decrease from 300 to 77 K was observed, and the luminescence color changed from green to blue. A considerable decrease (by 0.386 Å) in the unit cell parameters along the c axis was detected by X ray diffractometry when the temperature of the crystal decreased from 293 to 123 K. Shortening of the distances between the planes of adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 9 publications
(3 reference statements)
4
20
2
Order By: Relevance
“…1d and Table 1. Previously Mirochnik showed that C1 crystals display excimer fluorescence, 31 which is similar to C1 data here. With the exception of C2 which is considerably blue shifted relative to the powder, all other Cn SE films had nearly identical emission maxima to powder samples, with emission maxima blue shifting with increasing alkoxyl chain length.…”
Section: Solid-state Optical Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…1d and Table 1. Previously Mirochnik showed that C1 crystals display excimer fluorescence, 31 which is similar to C1 data here. With the exception of C2 which is considerably blue shifted relative to the powder, all other Cn SE films had nearly identical emission maxima to powder samples, with emission maxima blue shifting with increasing alkoxyl chain length.…”
Section: Solid-state Optical Propertiessupporting
confidence: 88%
“…For C1, the long lifetime (30.94 ns) and broad, structureless band have been attributed to excimer emission. 31 However, for C2-C18, much shorter lifetimes were observed (s pwo 32 ¼ 3-7 ns), suggesting different dye emissive species. Light reabsorption or light scattering associated with the bulk powder, [33][34][35] and aggregation effects (e.g.…”
Section: Solid-state Optical Propertiesmentioning
confidence: 96%
“…Unlike respective 1,3-dicarbonyl compounds, b-diketoboron difluorides shows an intensive luminescence both in solutions and in crystals [3]. This class of compounds is characterized by excimer luminescence observable as in solutions and as in crystals [4,5], moreover, luminescent thermochromism and size-dependent luminescence were observed in some crystals [6][7][8]. The optic properties of b-diketonatoboron difluorides crystals are closely connected with their molecular architecture [5,9].…”
Section: Introductionmentioning
confidence: 95%
“…16 For example, many difluoroboron dibenzoylmethane (dbm) derivatives show bathochromic shifts of ∼100 nm with ∼50 nm band width broadening. 17 In contrast, all three BF 2 AVB solids show very narrow band width emission relative to fluorescence in CH 2 Cl 2 [λ em ) 433 nm; full width at half-maximum (fwhm) ) 47 nm]. Among them, the dendritic solid formed by rapid solvent evaporation shows the most narrow emission band (fwhm ) 31 nm), with peak intensity at λ max ) 459 nm.…”
mentioning
confidence: 99%